Hemangiossarcoma cardíaco em cão: Relato de caso - Ferreira, A. R A; Oriá, A. P.; Moreira, E. L T; Silveira, C. P B; Marinho, T. C M S; Vieira Filho, C. H C V; Burguer, C. P. [UNESP]; Costa Neto, J. M. (My University, 2011)
Cardiac tumors are relatively rare in dogs, being hemangiosarcoma (HAS) the most common neoplasia. It consists in a primary, endothelial-originated neoplasia, which frequently compromises the right atrium. The pericardial effusion, frequently identified in dogs with heart HSA is responsible for the clinical signs, such as lethargy, exercise intolerance, dyspnea, and syncope. The diagnosis is difficult and suggested mainly by the clinic, hematologic, radiographic and echocardiographic findings, and was confirmed by histopathological examination. The present study aimed to report the presence of a heart HSA in a seven year old, spayed dog presented with signs of a congestive heart failure, due to the presence of a pericardial effusion secondary to tumor, and also lung, liver and spleen metastases. Despite this uncommon association a cardiac tumor should be suspected when signs of a heart failure, with rapid decline in the clinical status abruptly occurs.
Cardiac hemangiosarcoma in a dog: Case report
Keywords: Canine; Heart; Neoplasia; Canis familiaris; Syncope